A novel in vivo β carotene biosensor for heavy metals detection - Wong, Ling Shing; Lee, B. R.; Koh, C. E.; Ong, Y. Q.; Choong, C. W. (Triveni Enterprises, 2015)
A novel whole cell-based biosensor was constructed using Daucus carota cell as a biological component, with in vivo β-carotene as a reporter group. In this biosensor, the cells were immobilized using agarose gel, and change in in vivo β-carotene, before and after exposure of cells to heavy metals was noted using spectrophotometer at λ = 450 nm. Biosensor was found to operate at its optimum condition using cells from day-14 culture with density of 8 x 10(5) cells/cuvette, and immobilized with 0.5 % agarose at 45°C. The performance of biosensor was affected by pH with the best response produced at pH 7.5. Pb and Cu tests showed that biosensor was able to detect the presence of both heavy metals within the range of 0.01 ppm- 10.00 ppm. The performance of biosensor decreased in stability test with prolonged storage of 40 days, with a stable performance obtained after 10 days of storage. The results showed that β-carotene contain in naturally available cell D. carota responded well to the presence of heavy metals. It is a good indication that biosensor designed is a good candidate to be used for environmental toxicity assessment